2017
DOI: 10.1016/j.seizure.2016.11.029
|View full text |Cite
|
Sign up to set email alerts
|

The misdiagnosis of epilepsy: Appraising risks and managing uncertainty

Abstract: Diagnostic error is not entirely avoidable and a degree of uncertainty, and perforce risk, is intrinsic to the diagnostic process of epilepsy. The risks of a false negative diagnosis of epilepsy must be appraised against the also significant risks of a false positive diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
69
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 26 publications
(45 reference statements)
4
69
0
4
Order By: Relevance
“…However, data was collected retrospectively through medical reports from different neurologists, which may lead to a potential inter-observer variability in the initial diagnosis of NOS. The proportion of patients misdiagnosed as epilepsy at baseline observed in our study was nearly half of the numbers reported by previous authors, which is around 20% [10].…”
Section: Discussionsupporting
confidence: 52%
“…However, data was collected retrospectively through medical reports from different neurologists, which may lead to a potential inter-observer variability in the initial diagnosis of NOS. The proportion of patients misdiagnosed as epilepsy at baseline observed in our study was nearly half of the numbers reported by previous authors, which is around 20% [10].…”
Section: Discussionsupporting
confidence: 52%
“…An erster Stelle der Diagnostik steht die Frage, ob es sich tatsächlich um einen epileptischen Anfall gehandelt hat. Fehldiagnosen werden mit einer Häufigkeit von etwa 20 % angegeben [5] und betreffen insbesondere Menschen mit einer Synkope oder psychogenen nicht epileptischen Anfällen (▶ Tab. 1).…”
Section: Diagnostikunclassified
“…The rate of misdiagnosis of epilepsy remains high . This does not relate only to diagnosis of epilepsy itself, but also to the recognition of the epilepsy type and etiology, processes that may take several years.…”
Section: Epixchange: Recommendations For the Futurementioning
confidence: 99%
“…The rate of misdiagnosis of epilepsy remains high. 17 This does not relate only to diagnosis of epilepsy itself, but also to the recognition of the epilepsy type and etiology, processes that may take several years. Improved diagnostic techniques may be expensive, but a more accurate diagnosis would result in prompt application of correct treatments and, therefore, would be cost effective in the long term.…”
Section: Target-led Diagnostics Discoverymentioning
confidence: 99%